Determinación de la eficiencia de cinco fungicidas orgánicos y químicos en el control del oídio (leveillula taurica), del cultivo de Ají Jalapeño (capsicum annuum) en el cantón Urcuqui, provincia de Imbabura. - Potosí Recalde, Vicente Daniel (2014)
This research Project has been carried out in the Urcuqui area located in the Imbabura Province. The efficacy of five organic and chemical fungicides was determined. The treatment which presents the best efficacy in the control of oidium (leveillulia taurica) was determined, also the performance of production and the economic analysis of the treatments in every plot done with the organic fungicides (onion, stinging nettle, Equisetum arvense), and chemicals (miclobutanil and penconazol). The Complete Block Design Randomly (C.B.D.R.) was used with three repetitions and 11 treatments, meaningful tests, Tukey to the 5%, for treatments. Differences between the organic and chemical fungicides were detected (A x B) in the height of land to the 60 and 90 days, sickness incidence, efficacy of the treatment being used, weight of the fruit and performance Tm/ha..............